The Law Due to Authentic Degradation of Assets Against the Parties - Tommy Leonard (Journal of Morality and Legal Culture, 2020)
Degraded authentic deeds may cause losses to the parties. Notary as an official who is authorized by law has the responsibility for violations that cause the authentic deed to be degraded. In maintaining the professionalism of a notary, a notary who commits a violation can be given a sanction as a form of responsibility but also can file a lawsuit by the parties who suffer a loss. This thesis aims to determine the legal consequences of authentic deed degradation on the parties. The writing of this thesis uses a normative juridical research method or uses a statutory approach. Normative legal research is used to obtain rules, legal regulations and the application of the law. The notary's responsibility is given by imposing sanctions on the notary who commits the violation according to the level of the violation so that the notary can fulfill his responsibilities as a notary who has good morals and ethics in order to create justice for both the injured party and the notary itself.